The need to grow, learn and develop – how does management affect motivation for professional development? - Johannessen, Hilde Terese Drivenes (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
This article argues that knowledge management and social recognition is important for organisational learning and professional self-esteem in academic libraries. An anonymous survey was issued in 2016 to investigate how library staff’s self-esteem is affected by how they experience their management’s view and overview of their knowledge. The need for what Axel Honneth refers to as social recognition will also be discussed as an important part of how professional self-esteem and work satisfaction is experienced and further how this affects motivation to participate in professional development.